2276. Immunogenicity of Takeda's Bivalent Virus-Like Particle (VLP) Norovirus Vaccine (NoV) Candidate in Children From 6 Months up to 4 Years of Age. (26th November 2018) - Masuda, Taisei; Lefevre, Inge; Mendelman, Paul; Sherwood, Jim; Bizjajeva, Svetlana; Borkowski, Astrid
Abstract: Background: With the introduction of routine childhood rotavirus vaccination, norovirus is now becoming the major cause of medically-attended gastroenteritis in children. Takeda is developing a norovirus vaccine (NoV) that contains genotypes GI.1 and GII.4 consensus (GII.4c) sequence VLPs. We report the immunogenicity data of NoV administered to children from 6 months up to 4 years of age. Methods: Two age cohorts (1 to < 4 years, and 6 to < 12 months, n = 120 per cohort) were enrolled in this ongoing double-blind, randomized, phase 2 dose-finding study conducted in Colombia and Panama. Children received one or two intramuscular doses of NoV formulations containing 15/15, 15/50, 50/50 or 50/150 μg of GI.1/GII.4c VLPs adjuvanted with 0.5 mg Al(OH)3 . Vaccinations were on Days 1 and 29, with saline placebo as dose two to maintain blinding in one dose groups. Antibody responses to each VLP were measured on days 1, 29 and 57 as functional histo-blood group binding antigen blocking antibodies (HBGA), expressed as seroresponse rates (SRR), the proportions displaying ≥ 4-fold increases over baseline, and geometric mean titres (GMT). Results: Each formulation induced dosage-dependent HBGA responses after a single dose, with a further increase after a second dose. In 1- to <4 year-olds HBGA SRR against GI.1 and GII.4c after one dose were 55–62% and 67–82%, respectively. SRR increased to 93–100% and 83–100% after a second dose. In 6 to < 12 month-olds responses were lower after the first dose: SRRs were 10–61% and 17–65% for GI.1 and GII.4c, respectively, increasing to 83–100% and 80–92% after a second dose. GMTs reflected this pattern of responses with higher GMTs for GI.1 and GII.4c achieved with the 50/150 μg formulation than the other dosages after both vaccinations in both age cohorts. Conclusion: In 6–12 month-old infants and children up to 4 years of age, robust immune responses to the bivalent norovirus VLP vaccine candidates were observed; the highest HBGA responses in both age cohorts were observed after two doses of the 50/150 μg formulation. Further clinical evaluation of these formulations is underway in infants < 6 months of age. Clinical Trial Registration (NCT: 02153112, EudraCT: 2014-000778-20) Disclosures: T. Masuda, Takeda Pharmaceuticals International AG: Employee, Salary. I. Lefevre, Takeda Pharmaceuticals International AG: Employee, Salary. P. Mendelman, Takeda Pharmaceuticals International AG: Employee, Salary. J. Sherwood, Takeda Pharmaceuticals International AG: Employee, Salary. S. Bizjajeva, Takeda Pharmaceuticals International AG: Employee, Salary. A. Borkowski, Takeda Pharmaceuticals International AG: Employee, Salary.